Respuestas

2013-08-20T00:32:58+02:00

Sean los números A y B, A>B
Del enunciado
                       A + B = 115     (1)
                           2A = 3B       (2)
           De (1): A = 115- B
           En (2):
                     2(115 - B) = 3B
                       230 - 2B = 3B
                             230 = 5B
                                B = 230/5                    B = 46
           En (1):
                        A + 46 = 115
                               A = 115 - 46
                               A = 69
Los números son 69 y 46